Odpowiedzi

2010-02-13T01:00:57+01:00
A)
x²+x/3=0
a=1, b=⅓, c=0
Δ=b²-4ac
Δ=1/9
√Δ=⅓

x₁=(-b-√Δ)/2a (ułamek)
x₁=(-⅓-⅓)/2
x₁=-⅔*2
x₁=-⅓

x₂=(-b+√Δ)/2a (ułamek)
x₂=(-⅓+⅓)/2
x₂=0

b)
x²+6x+9=0
a=1, b=6, c=9
Δ=b²-4ac
Δ=36-36
Δ=0
x=(-b)/2a (ułamek)
x=-6/2
x=-3

c)
x²+6x=7
x²+6x-7=0
a=1, b=6, c=-7
Δ=b²-4ac
Δ=36+28
Δ=64
√Δ=8
x₁=(-b-√Δ)/2a (ułamek)
x₁=(-6-8)/2
x₁=-7

x₂=(-b+√Δ)/2a (ułamek)
x₂=(-6+8)/2
x₂=1

d)
3x²+2x-2=0
a=3, b=2, c=-2
Δ=b²-4ac
Δ=28
√Δ=2√7

x₁=(-b-√Δ)/2a (ułamek)
x₁=(-2-2√7)/6
x₁=-⅓-⅓√7

x₂=(-b+√Δ)/2a (ułamek)
x₂=(-2+2√7)/6
x₂=-⅓+⅓√7

e)
2x=5x²+1
5x²-2x+1=0
a=5, b=-2, c=1
Δ=b²-4ac
Δ=4-20
Δ=-16
BRAK ROZWIĄZAŃ

f)
2-4x=3x²
3x²+4x-2=0
a=3, b=4, c=-2
Δ=b²-4ac
Δ=16+24
Δ=40
√Δ=2√10

x₁=(-b-√Δ)/2a (ułamek)
x₁=(-4-2√10)/6
x₁=2(-2-√10)/6
x₁=-⅔-⅓√10

x₂=(-b+√Δ)/2a (ułamek)
x₂=(-4+2√10)/6
x₂=2(-2+√10)/6
x₂=-⅔+⅓√10